If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1(2x + -5) = 4x + -1(x + 42) Reorder the terms: X + -1(-5 + 2x) = 4x + -1(x + 42) X + (-5 * -1 + 2x * -1) = 4x + -1(x + 42) X + (5 + -2x) = 4x + -1(x + 42) Reorder the terms: 5 + X + -2x = 4x + -1(x + 42) Reorder the terms: 5 + X + -2x = 4x + -1(42 + x) 5 + X + -2x = 4x + (42 * -1 + x * -1) 5 + X + -2x = 4x + (-42 + -1x) Reorder the terms: 5 + X + -2x = -42 + 4x + -1x Combine like terms: 4x + -1x = 3x 5 + X + -2x = -42 + 3x Solving 5 + X + -2x = -42 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + X + -5 + -2x = -42 + -5 + 3x Reorder the terms: 5 + -5 + X + -2x = -42 + -5 + 3x Combine like terms: 5 + -5 = 0 0 + X + -2x = -42 + -5 + 3x X + -2x = -42 + -5 + 3x Combine like terms: -42 + -5 = -47 X + -2x = -47 + 3x Add '2x' to each side of the equation. X + -2x + 2x = -47 + 3x + 2x Combine like terms: -2x + 2x = 0 X + 0 = -47 + 3x + 2x X = -47 + 3x + 2x Combine like terms: 3x + 2x = 5x X = -47 + 5x Simplifying X = -47 + 5x
| [-2x+22-3z]=[6x-2y+45] | | 4=3h-2 | | G-10=-9g+10 | | -2(b+3)=16 | | 3b^2-2b+16=0 | | x+(x+15)=44 | | a-2-5=0 | | 5x+12=2x+354 | | 1(1-3x)=2(-4x+7) | | 6x-8-7=3x+1+x | | 9x+3-10=3(3x+3) | | -2(b+3)=15 | | -8x-55=2x+75 | | 8x-2=-9+1x | | 4(3m+1)=8m+20 | | 5-(3x+9)-2x=15x-2(x-5) | | 3n+7=-2n+17 | | .6x+3=27 | | m/4-8=10 | | 2x-7+4x+1=12 | | Y=4.5x+12 | | [4x+42]=[24+6y] | | 0.9(220-a)=178.2 | | 5w+1=0 | | 2-7p-2=2p+9 | | X+3x+2x=x | | 13x+4x+3+6=10+27+3x | | 11-c=7 | | y+7=.33(x+2) | | 3(m+4)=7m-8 | | 2.25*1.8= | | -34-7x=-4x+44 |